2021
DOI: 10.17650/1683-3295-2021-23-1-16-25
|View full text |Cite
|
Sign up to set email alerts
|

Radiosurgical treatment of medically refractory Parkinson’s tremor

Abstract: Introduction. In spite of medication treatment being today the basic form of treatment for Parkinson’s disease, surgical methods may be preferable to improve symptoms of the disease. Radiosurgery is one of them, but in Russia, to date, there are no publications summarizing data about the experience of using this method throughout the country.The study objective is to evaluate the effect of radiosurgical thalamotomy (destruction of the intermediate ventral nucleus of the thalamus) on the severity of tremor in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…There was no significant difference in any one group (P > 0:05). There was 1 case of lower extremity deep vein thrombosis in the control group and no case of lower extremity deep vein thrombosis in the intervention group, 6 Scanning which was less in both groups. Firstly, it may be closely related to the high attention paid by medical staff, and secondly, it may be related to the small sample size of the study, which still needs to be confirmed by studies with large samples in the future.…”
Section: Experiments and Analysismentioning
confidence: 82%
See 1 more Smart Citation
“…There was no significant difference in any one group (P > 0:05). There was 1 case of lower extremity deep vein thrombosis in the control group and no case of lower extremity deep vein thrombosis in the intervention group, 6 Scanning which was less in both groups. Firstly, it may be closely related to the high attention paid by medical staff, and secondly, it may be related to the small sample size of the study, which still needs to be confirmed by studies with large samples in the future.…”
Section: Experiments and Analysismentioning
confidence: 82%
“…Ivanov et al stated that NSS uses a high-performance computer to closely correlate patient preoperative image data (MRI and CT) with the actual location of intraoperative lesions. Surgeons can display three-dimensional (3D) images of surgical sites and instruments in real time through a monitoring screen [ 6 ]. Aibar-Duran et al said that preoperative imaging often fails to provide accurate guidance to the surgeon due to changes in the patient's position or surgical environment [ 7 ].…”
Section: Literature Reviewmentioning
confidence: 99%